Iklim Komunikasi Antar Umat Beragama Dalam Selimt Suariat Islam Kabupaten Aceh Tenggara - Adib, Shahibul (Tasamuh: Jurnal Studi Islam, 2015)
Thise article explores the support and resist of communication between ummah in the religions in Noth Aceh, Cane city. Metodology of this reseach is discribtive analisis. This reseach is quantitative with interview dan observation. The condition of communication between Umat in Aceh Cane has connection from the last time. They built everday by the good attitude each other. The plurality of the religion is no effect. In the persepective, we are the same each other in search. There are many try in the world. From the first time Islamic laws application, the minority have undertand about their position. There are conflict rising among them. This article tries to answer this problem, how can they build effective communication each other.